COVID-19 Crisis: The Pandemic Highlights the Unique Training and Skills of Military Physicians Afforded by Military-Specific Graduate Medical Education. Issue 11 (23rd July 2021) - Shahbodaghi, David; Farnell, Edwin
ABSTRACT: Military physicians trained in military Graduate Medical Education programs are uniquely prepared to lead in austere and chaotic environments based on formal and informal curricula taught in military treatment facilities. The coronavirus disease-2019 pandemic highlighted this reality when military-trained physician leaders were challenged to lead change directly from the front.